New Insights into Drug Reaction with Eosinophilia and Systemic Symptoms Pathophysiology - Musette, Philippe; Janela, Baptiste (Frontiers in Medicine, 2017)
Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) also called Drug-Induced Hypersensitivity Syndrome (DIHS) is a severe type of cutaneous Drug Induced Eruption (DIE). DRESS may be a difficult disease to diagnose since the symptoms mimic those of cutaneous and systemic infectious pathologies and can appear up to 3 months after the initial culprit drug exposure. Patient symptoms that allow a diagnosis of DRESS include rash development after a minimum of 3 weeks after the onset of a new medication, associated with facial edema, lymphadenopathy, and fever. Biological findings include liver abnormalities, leukocytosis, eosinophilia, atypical lymphocytosis, and reactivation of certain human herpes viruses. In DRESS, liver, kidneys and lungs are frequently involved in disease evolution. Patients with serious systemic involvement are treated with oral corticosteroids and full recovery is achieved in the majority of cases. DRESS is a rare disease, and little is known about factors that predict DRESS occurrence. The key features of this reaction are eosinophil involvement, the role of the culprit drug, and virus reactivation that trigger an inappropriate systemic immune response in DRESS patients. Interestingly it was evidenced that at-risk individuals within a genetically restricted population shared particular HLA loci. In this respect a limited number of well-known drugs are able to induce DRESS. The present review describes the up to date advances in our understanding of the pathogenesis of DRESS.